2013
DOI: 10.1007/s00228-013-1555-z
|View full text |Cite
|
Sign up to set email alerts
|

Persistence to antihypertensive drug treatment in Swedish primary healthcare

Abstract: Major determinants of discontinuation of antihypertensive drug treatment are male sex, young age, mild-to-moderate systolic blood pressure elevation, and birth outside of Sweden.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
34
2
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(41 citation statements)
references
References 47 publications
3
34
2
2
Order By: Relevance
“…Studies have suggested that across both developed and LMIC countries there are considerable problems with adherence to antihypertensive medicines [18][19][20][21][22][23]. Overall, only approximately 14 to 25 % of treated patients achieve optimal blood pressure control, with 50 % of patients appearing to stop taking their antihypertensive treatments within the first year [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have suggested that across both developed and LMIC countries there are considerable problems with adherence to antihypertensive medicines [18][19][20][21][22][23]. Overall, only approximately 14 to 25 % of treated patients achieve optimal blood pressure control, with 50 % of patients appearing to stop taking their antihypertensive treatments within the first year [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, persistence to antihypertensive therapy is increased in the presence of cardiovascular comorbidities. 13,32 Also, at the time of the study a blood pressure o130/80 mm Hg was recommended in patients with diabetes and cardiovascular disease. 33 An educational level of 10-12 years, being native Swede and the presence of psychiatric disorder increased the likelihood of reaching target blood pressure in women.…”
Section: Discussionmentioning
confidence: 99%
“…12 In Sweden, patients born abroad have the lowest persistence to antihypertensive treatment. 13 If there is a difference in prescription pattern according to educational level and country of birth in women and men is not known. Furthermore, whether educational level and country of birth influence achieved target blood pressure differently in women and men is not known.…”
Section: Introductionmentioning
confidence: 99%
“…In the aftermath of this study, the question of antihypertensive drug adherence has again attained much interest. It has been shown that the persistence to antihypertensive treatment for newly diagnosed patients with hypertension decrease by 26% after 1 year . It has also been described that 50% off apparently treatment‐resistant hypertensive patients have low medication adherence as the cause of TRH .…”
Section: Introductionmentioning
confidence: 99%